Assessing media education a resource handbook for educators and administrators - Christ, William G. (Mahwah, N.J. : L. Erlbaum, 2006)
"Assessing Media Education provides guidelines for media educators and administrators in higher education media programs who are creating or improving student-learning assessment strategies. Covering the topics and categories established by the Accrediting Council on Education in Journalism and Mass Communications, this resource guides readers through the steps of developing an assessment plan, establishing student-learning outcomes in the various areas of the curriculum, and measuring those outcomes." "As assessment gains importance throughout the curriculum, Assessing Media Education will be a useful and practical resource for media educators and administrators as they grapple with the challenges of assessment."--BOOK JACKET.
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mass media -- Study and teaching (Higher) -- Evaluation -- Handbooks, manuals, etc; Electronic books